In utero ultrasound diagnosis of corpus callosum agenesis leading to the identification of orofaciodigital type 1 syndrome in female fetuses. Issue 4 (28th November 2017) - Alby, Caroline; Boutaud, Lucile; Bonnière, Maryse; Collardeau‐Frachon, Sophie; Guibaud, Laurent; Lopez, Estelle; Bruel, Ange‐Line; Aral, Bernard; Sonigo, Pascale; Roth, Philippe; Vibert‐Guigue, Claude; Castaigne, Vanina; et al.
Abstract : Background: OFD1 syndrome is a rare ciliopathy inherited on a dominant X‐linked mode, typically lethal in males in the first or second trimester of pregnancy. It is characterized by oral cavity and digital anomalies possibly associated with cerebral and renal signs. Its prevalence is between 1/250, 000 and 1/50, 000 births. It is due to heterozygous mutations of OFD1 and mutations are often de novo (75%). Familial forms show highly variable phenotypic expression. OFD1 encodes a protein involved in centriole growth, distal appendix formation, and ciliogenesis. Cases: We report the investigation of three female fetuses in which corpus callosum agenesis was detected by ultrasound during the second trimester of pregnancy. In all three fetuses, fetopathological examination allowed the diagnosis of OFD1 syndrome, which was confirmed by molecular analysis. Conclusions: To our knowledge, these are the first case reports of antenatal diagnosis of OFD1 syndrome in the absence of familial history, revealed following detection of agenesis of the corpus callosum. They highlight the impact of fetal examination following termination of pregnancy for brain malformations. They also highlight the contribution of ciliary genes to corpus callosum development.